2015
DOI: 10.1186/s12864-015-1652-8
|View full text |Cite
|
Sign up to set email alerts
|

The Streptomyces leeuwenhoekii genome: de novo sequencing and assembly in single contigs of the chromosome, circular plasmid pSLE1 and linear plasmid pSLE2

Abstract: BackgroundNext Generation DNA Sequencing (NGS) and genome mining of actinomycetes and other microorganisms is currently one of the most promising strategies for the discovery of novel bioactive natural products, potentially revealing novel chemistry and enzymology involved in their biosynthesis. This approach also allows rapid insights into the biosynthetic potential of microorganisms isolated from unexploited habitats and ecosystems, which in many cases may prove difficult to culture and manipulate in the lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 47 publications
4
68
0
1
Order By: Relevance
“…It is especially interesting that the new compounds, lentzosides A-F, are derived from a novel Lentzia strain as previously new specialized metabolites from Atacama Desert actinomycetes have come from novel Streptomyces strains, 7 notably from a deep seated 16S rRNA gene clade that can be equated with the species, Streptomyces leeuwenhoekii. [10][11][12][13][14][15][16] The genus Lentzia was validly published in 1995, 25 but to date does not appear to have been studied in terms of its natural product chemistry, though Lentzia sp. 7887 effects the biotransformation of FR901459, a novel derivative of cyclosporin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is especially interesting that the new compounds, lentzosides A-F, are derived from a novel Lentzia strain as previously new specialized metabolites from Atacama Desert actinomycetes have come from novel Streptomyces strains, 7 notably from a deep seated 16S rRNA gene clade that can be equated with the species, Streptomyces leeuwenhoekii. [10][11][12][13][14][15][16] The genus Lentzia was validly published in 1995, 25 but to date does not appear to have been studied in terms of its natural product chemistry, though Lentzia sp. 7887 effects the biotransformation of FR901459, a novel derivative of cyclosporin.…”
Section: Discussionmentioning
confidence: 99%
“…C38 and the cell invasion inhibitor chaxapeptin from S. leeuwenhoekii strain C58. [10][11][12][13][14][15][16] As part of our ongoing program to investigate the extremobiosphere as a source of new natural products, we have focused our attention on Lentzea sp. strain H45 which was isolated from a high-altitude Atacama Desert soil and shown to produce a specific pattern of secondary metabolites based on its liquid chromatography MS (LCMS) profile and associated NMR data.…”
Section: Introductionmentioning
confidence: 99%
“…The most gifted strains could be targeted for complete genome sequencing, which is now feasible and relatively inexpensive by using a combination of Illumina and PacBio sequencing. 16,[52][53][54] By adding additional CP-TEs from other taxons, the CP-TE multi-probe approach can be adapted to survey draft genomes of other bacteria with large genomes, such as species of the Myxobacteria, Burkholderia and Photorhabdus, all of which have gifted members that encode multiple SMGCs. 16 …”
Section: Discussionmentioning
confidence: 99%
“…However, initial inspection of this sequence using Artemis (Rutherford et al 2000), and particularly the GC Frame Plot option contained within it (Bibb et al 1984), revealed many likely mis-assemblies in contigs containing modular type I polyketide synthase (PKS) and non-ribosomal peptide synthetase (NRPS) genes. The short-size of the quality reads obtained from high mol% GC DNA (streptomycetes generally possess a GC content of around 73 mol% G?C) using Illumina sequencing (generally less than 250 nt) hampers the correct assembly of the repetitive regions characteristic of these genes Gomez-Escribano et al 2015, 2016. We thus set out to establish a high-quality genome sequence of S. leeuwenhoekii C34 T by combining two next generation sequencing technologies: the second-generation Illumina MiSeq renowned for very accurate short nucleotide-reads and the third-generation Single Molecule, Real-Time (SMRT) sequencing platform from Pacific Biosciences (PacBio) that gives long, but less accurate, nucleotide-reads (in our experience with Streptomyces DNA, around 5 kb on Antonie van Leeuwenhoek average after quality filtering) .…”
Section: S Leeuwenhoekii Strain C34mentioning
confidence: 99%
“…Gene clusters for desferrioxamine E (sle44550 to sle44600) and ectoine (sle52690 to sle52700) biosynthesis were also identified using antiSMASH version 2.0 (Blin et al 2013;Gomez-Escribano et al 2015;Razmilic 2017).…”
Section: Gene Clusters For Other Specialised Metabolitesmentioning
confidence: 99%